Numerical stability assessment of a mining slope using the synthetic rock mass modeling approach and strength reduction technique - Teng, Lin; He, Yuanyuan; Wang, Yan; Sun, Changze; Yan, Jianhua (Frontiers in Earth Science, 2024)
Structurally controlled slope failure in open-pit mining occurs when the shear stress acting on the geological structure exceeds its shear strength. Mining slope stability is an extremely important topic from the ramifications of safety, social, economic, environmental and regulatory factors. This study reports the engineering geological setting of a bedded mining slope in China, and evaluates its stability via a numerical approach. First, a slope profile model is constructed using a synthetic rock mass (SRM) modeling approach. More specifically, the mechanical behavior of colluvium, intact rock and discontinuities are represented by linear contact model, bonded particle model and smooth joint model, respectively. Then, the factor of safety (FOS) and instability process are investigated by integrating the discrete fracture network (DFN)-distinct element method (DEM) and strength reduction technique (SRT). In addition, shear stress analyses of colluvium and bedrock are conducted for revealing the potential failure mechanism. Finally, the well-established limit equilibrium (LEM) and finite element method (FEM) are adopted for simulation results comparison and validation.